2009
DOI: 10.1104/pp.109.149369
|View full text |Cite
|
Sign up to set email alerts
|

TheRON1/FRY1/SAL1Gene Is Required for Leaf Morphogenesis and Venation Patterning in Arabidopsis

Abstract: To identify genes involved in vascular patterning in Arabidopsis (Arabidopsis thaliana), we screened for abnormal venation patterns in a large collection of leaf shape mutants isolated in our laboratory. The rotunda1-1 (ron1-1) mutant, initially isolated because of its rounded leaves, exhibited an open venation pattern, which resulted from an increased number of free-ending veins. We positionally cloned the RON1 gene and found it to be identical to FRY1/SAL1, which encodes an enzyme with inositol polyphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 89 publications
(135 reference statements)
1
91
0
Order By: Relevance
“…Hence, we hypothesized that the auxin-related phenotypes of ron3 are the consequence of altered PIN phosphorylation status and activity. Additional support came from the resemblance of the ron3 phenotypes to those of ron1, for which defective PIN polarity had been shown (14). The additive phenotypes in the double-mutant ron1 ron3 indicated that RON3 acts in a mode similar to that of RON1, corroborating a role for RON3 in PIN polarity-related processes.…”
Section: Ron3 Has a Function In The Dephosphorylation Dynamics Of Thementioning
confidence: 83%
See 2 more Smart Citations
“…Hence, we hypothesized that the auxin-related phenotypes of ron3 are the consequence of altered PIN phosphorylation status and activity. Additional support came from the resemblance of the ron3 phenotypes to those of ron1, for which defective PIN polarity had been shown (14). The additive phenotypes in the double-mutant ron1 ron3 indicated that RON3 acts in a mode similar to that of RON1, corroborating a role for RON3 in PIN polarity-related processes.…”
Section: Ron3 Has a Function In The Dephosphorylation Dynamics Of Thementioning
confidence: 83%
“…The A. thaliana (L.) Heynh. lines are Ler and Col accessions (Nottingham Arabidopsis Seed Collection), ron3-1 and ron1-1 mutants (both Ler) (14), ron3-2 allele (GK374F12 line, homozygous for the T-DNA insertion in At4g24500; Col), rcn1 mutant (WS) (10), 35S::PID, and line PID21 (Col) (20,21). Media and growth conditions are discussed in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,[17][18][19][20] Previously, we reported that HY5, a well-characterized component in the light signal transduction pathway, also mediates ABA response during seed germination and lateral root development. 21,22 Using the enhanced light response as a phenotype, we conducted a genetic screen and isolated fry1 suppressors with reduced light sensitivity.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Phytohormone-dependent controls are not included in this review; readers interested in those controls may wish to consult the latest reviews on the roles for each phytohormone in the Arabidopsis Book. Understanding of genetic controls in tissue-or cell-type differentiations such as in leaf venation patterning has also advanced in recent years (e.g., Dengler and Kang 2001;Alonso-Peral et al 2006;Robles et al 2010), but these topics will be covered in another review article.…”
Section: Introductionmentioning
confidence: 99%